Minimally invasive access cavities in endodontics - Abdulrazaq, Lubna A; Ali, Ahmed H; Foschi, Federico (Journal of Baghdad College of Dentistry, 2023)
Background: The access cavity is a critical stage in root canal therapy and it may influence the subsequent steps of the treatment. The new minimally invasive endodontic access cavity preparation concept aims to preserve sound tooth structure by conserving as much intact dentine as possible including the pulp chamber's roof, to keep the teeth from fracturing during and after endodontic treatment. While there is great interest in such access opening designs in numerous publications, still there is a lack of scientific evidence to support the application of such modern access cavity designs in clinical practice. This review aims to critically examine the literature on minimal access cavity preparations, explain the effect of minimally invasive access cavity designs on various aspects of root canal treatment, and identify areas where additional research is required. Data: An electronic search for English-language articles was performed using the following databases: Google Scholar, PubMed, and Research Gate. The following keywords were used: "minimally invasive access cavity", "conservative endodontic cavity ", and "classification of access cavity". Study selection: 64 papers that were the most relevant to the topics in this review were selected between 1969 to 26 February 2022. Conclusions: Minimally invasive access cavities can be classified into conservative, ultraconservative, truss access, caries and restorative-driven cavities. There is a deficiency of proof that a minimally invasive access cavity maintains the resistance to fracture of endodontically treated teeth greater than traditional access cavities. There was no difference in the percentage of untouched walls and debris removal in teeth with conservative vs traditional access cavities, however, truss and ultraconservative access cavities resulted in poor irrigation efficacy compared to traditional ones. Also, the lower cyclic fatigue resistance of rotary instruments and root canal obturation with voids were associated with minimally invasive access cavities. The studies about minimally invasive access cavities still have a wide range of methodological disadvantages or register unsatisfactory or inconclusive results. Therefore, further research on this topic is needed especially with the everyday advancement of techniques and armamentarium used in endodontics.